Repeated high-intensity running and sprinting in women's football competition - Spencer, M.; Wiig, H.; Gabbett, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Despite the reported importance of high-intensity running (Mohr et al., 2005) and repeated-sprint ability (Gabbett et al., 2008) to competitive success in football, studies investigating the nature of repeated high-intensity activity in games are limited (Gabbett et al., 2008). To our knowledge, no study has investigated the concurrent repeated, high-intensity (RHIA) and repeatedsprint activity (RSA) of intermittent team sport competition. Therefore, the aim of this study is to describe the nature of RSA and RHIA (e.g. striding and sprinting activities) that involve a high energy cost and are associated with short duration (i.e. .20 seconds) recovery periods. Methods: Thirteen elite women football players underwent video-based time-motion analysis on 34 occasions during national and international standard matches, in which all players played 90 min. RSA and RHIA were defined as successive (i.e. 2 or more) sprints, or striding and sprinting efforts that occurred with .20 seconds between efforts. Results: The number of RSA and RHIA bouts performed was similar between the first and second half of matches, when analysed as sets of 2, 3, 4, 5 or 6 efforts. Sprinting and striding/sprinting durations tended to remain relatively stable irrespective of the number of efforts in a RSA or RHIA bout, or the period of play. However, the mean recovery duration progressively increased with a greater number of efforts per bout; RSA (sets of 2: 9.94 ± 4.73; sets of 6: 16.57 ± 2.49; Effect Size (ES) = 1.75, large) and RHIA (sets of 2: 9.49 ± 2.60; sets of 6: 14.74 ± 2.66; ES = 2.00, large). Furthermore, RSA bouts were associated with moderately greater recovery durations between efforts (ES = 0.67-0.93) for sets of 4 and 5 sprints, in the second half compared to the first half of matches. However, only trivial or small differences (ES = 0.01-0.33) were observed between halves for RHIA bouts. Discussion: These findings suggest that first to second half reductions in RHIA and RSA do not occur in elite Women's soccer competition. However, players increase the amount of low-intensity recovery performed between RHIA and RSA efforts, most likely in an attempt to maintain RHIA and RSA performance. These findings are novel and emphasize the importance of repeated-effort ability to elite Women's football, and highlight the importance of training this quality to minimise reductions in performance during competitive matchplay.